International accreditation of a pediatric hematology/oncology fellowship program in Guatemala: a quantitative assessment - Daniel C. Moreira; Claudia Garrido; Roy Rosado; Leeanna Fox Irwin; Ricardo Mack; Carlos Rodriguez-Galindo; Federico Antillón-Klussmann (BMC Medical Education)
Abstract Purpose High-quality graduate medical education programs are essential to expand the care available to children with cancer worldwide. The authors used the Education Program Assessment Tool (EPAT), a standardized tool for evaluating pediatric hematology/oncology (PHO) fellowship programs, to describe the impact of the Accreditation Council for Graduate Medical Education International (ACGME-I) accreditation process. Methods The EPAT is a comprehensive, validated tool for evaluating the elements of PHO fellowship programs. The authors used the EPAT in May 2018 and December 2023 to compare the pre-accreditation and post-accreditation status of the Unidad Nacional de Oncología Pediátrica (UNOP) PHO fellowship program. Results The authors used the EPAT to identify program gaps and to prioritize interventions to meet ACGME-I accreditation standards. Before accreditation, the overall score of the UNOP PHO fellowship program was 77.2%. The highest score was for Hospital Infrastructure (86.4%) and the lowest score was for Research (63.0%). After accreditation, the overall score was 88.3%. Eight of the 10 EPAT domains had higher post-accreditation scores, with a significant improvement in domain scores overall (P < 0.0001) (Fig. 2). In alignment with the improvement workstreams, the Educational Infrastructure and Evaluation domains had the greatest increases in scores (27% and 25%, respectively). Research continued to have the lowest score (75.9%), but this was improved by 13%. Conclusions This study provides quantitative data on the enhancement of a PHO fellowship program in a middle-income country after the process ACGME-I accreditation based on the improvement of EPAT scores. Additional analyses and evaluation tools are needed to identify strategies optimize training approaches and to meet the evolving accreditation standards for health care around the world.